PROUNI COMO VIA DE ACESSO À EDUCAÇÃO SUPERIOR: ENTRE A DEMOCRATIZAÇÃO E A EXPANSÃO DO ENSINO PRIVADO - PRADO, MARCIANO DO (2020)
The present research exposes an analysis of the “Programa Universidade para Todos” (PROUNI), one of the government policy of access to undergraduate degree, implemented since 2005, in Brazil. The motivation of this search follows to the premise assumed by PROUNI to democratization of undergraduate education through the granting of full and partial scholarships in private educational institutions. It is proposed to answer the following question: How did PROUNI try to promote the democratization of undergraduate in Brazil? It started by the hypothesis that PROUNI can be understood through the bias of the class conciliation policy, where different interests are served with implementation of this policy: as the profitable private education’s sector, as well the subordinate classes that hope the opportunity of educational rights access, by a popular basis’ government, who’s has been denied until then. This research is based on a qualitative methodology, by a descriptive analysis, as documentary as bibliographic. It is proposed the analysis of the documents that constituted the Legislation nº 11.096 of January 2005, discussing the main changes that occurred in your project, from the forces and social groups that acted in its approval process. Then, it is analyzed the criticisms about the main deficiencies of this program, indicating it as a mechanism of indirect transfer of public resources to the private sector. The liberal concept of citizenship, from the perspective of Thomas Marshall, is considered as a possibility of participation and integration in social structures, although it identifies limits to the construction of these ideals in the context of capitalist society, especially in the neoliberal context. It is considered the access to education as a basis for expanding citizenship rights, from the perspective of Anísio Teixeira and Antônio Cunha. The research is based on Antonio Gramisci’s historical and dialectical materialism teory, considering possibilities of gaps in the structures of capitalism as opportunities for social transformations through the construction of consensus. The analysis of the development and results of PROUNI was conducted by the junction of official data and search indexes that highlight impacts, changes and limits identified in this policy of access to undergraduate, and concluded that PROUNI is characterized as a policy of class reconciliation.